The Effect of Allowance and Fast-Food Consumption on the Obesity of Adolescents in Badung Regency, Bali - Paseru, Ludgardis Vicky; Kasmini, Oktia Woro; Rustiana, Eunike Raffy (Public Health Perspective Journal, 2021)
The obesity is a condition of excessive fat in the body that can have a significant effect on health. The excess consumption of fast food can cause excess fat in the body. The high amount of the allowance makes the adolescents easier to consume the fast food which is reachable. This study aims to analyze the direct and indirect effect of allowance on obesity through consumption of fast food. This research is a quantitative study with a case control study approach. A sample of 100 respondents consisting of 20 case samples and 80 control samples were obtained by using fixed disease sampling technique. Data analysis used chi square test and multivariate analysis. The results obtained were that pocket money had a direct effect on the incidence of obesity (b = 1.4; 95% CI = 0.54 to 2.25; p = 0.001). This allowance has an indirect and significant effect on the incidence of obesity through consumption of fast food (b = 1.3; 95% CI = 0.17 to2.43; p = 0.024). The consumption of fast food has a direct effect on obesity with values (b = 1.55; 95% CI = 0.38 to 2.71; p = 0.009). The conclusion of this study is allowance has a direct and indirect effect on adolescent obesity. The results of this study are expected to become a reference for related parties in improving nutritional problems (obesity), particularly in controlling the allowance and consumption of fast food among adolescents.